PENGARUH PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP PERTUMBUHAN EKONOMI PADA KABUPATEN/KOTA DI SULAWESI TENGAH - Fauzan, Muhammad; Amir, Andi Mattulada; Kahar, Abdul (Katalogis, 2018)
The Research aims to test and analyze simultaneous and partial influences of local revenue and equalization funds on the economic growth in regencies/cities in Central Sulawesi. Population consist of 13 regencies/cities in Central Sulawesi. By using purposive sampling method, there are 11regencies/cities that meet the requirements the study. Data used is secondary data that ranges 4 year period from 2012-2015. Research method is descriptive with verificative approach. Analysis tool is multiple regression analysis. The study finds that local revenue, equalization funds, and economic growth in regencies/cities in Central Sulawesi show positive increases from year to year. Regression analysis shows that local revenue and equalization funds simultaneously have positive and significant influence on the regencies/cities in Central Sulawesi; local revenue has positive and significant on regencies/cities economic growth, while equalization funds has positive but insignificant influence on regencies/cities economic growth in Central Sulawesi.